Earth observation by satellite Telsat 4. (Brussels : Federal science policy office, 2002)
Summary: Following on the commitments made by Belgium to the European Space Agency(ESA) and to the French "Satellites Pour l'Observation de la Terre"(SPOT)programme, a national satellite remote sensing research programme, calledTELSAT,was set up in 1986. The main objective was the building up of a Belgianexpertise inspatial earth observation techniques and applications, and to develop arecurrentmarket with regard to the use of satellite data. TELSAT has since evolvedfrom anexploratory phase (TELSAT I, 1985-1989), over a phase of development ofapplications (TELSAT II, 1989-1993) to a phase addressing concrete userinformation needs (TELSAT III, 1993-1996). The fourth phase of theprogramme,called TELSAT 4 (1996-2000), was part of the Sustainable DevelopmentProgramme.This report covers the main results of the projects funded by OSTC'sTELSAT 4programme.
Keywords: Remote sensing -- Equipment and supplies; Aardobservatiesatellieten; Ecologie